Two new species of the rare Neotropical caddisfly genus Amphoropsyche Holzenthal (Trichoptera, Leptoceridae) - Razuri-Gonzales, E (2017)
The authors wish to thank Santiago Villamarín and Christian Villamarín for their hospitality and support during our field studies in Carchi, Ecuador during February of 2017. Xavier Amigo, Nature Experience, and Jolanda Huisman also provided very generous support in the field. This study was supported by Universidad de Las Americas project AMB.BRT.17.005 “Diversidad y Distribucion de Trichoptera de Ecuador,” Minnesota Agricultural Experiment Station projects MIN-17-017 and 17-029, and USDA National Institute of Food and Agriculture project 1013092. ERG was funded through a doctoral fellowship from Cienciactiva, Consejo Nacional de Ciencia, Tecnologia, e Innovacion Tecnologica Peru (contract 277-2015- FONCECYT). The Ministerio del Ambiente, Ecuador, granted the study permit (MAE-DNB-CM-2016-0045). This support is gratefully acknowledged. We thank Dr Brian Armitage, Dr Tatiana Arefina-Armitage, Dr Ana Previsic, and an anonymous reviewer for providing very useful suggestions to improve the manuscript.